Clinical utility of the PBAC score in quantifying treatment response to hysteroscopy: a retrospective observational study - Öz, Ömer Faruk; Dinç, Can; Öğüt, Burhan; Arıkan, Saltuk Buğra; Doğan, Selen; Özekinci, Murat; Mendilcioğlu, İnanç (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical utility of the Pictorial Blood Loss Assessment Chart (PBAC) as a quantitative tool for measuring treatment response in patients undergoing hysteroscopy for abnormal uterine bleeding (AUB), and to examine its correlation with changes in hemoglobin levels, endometrial thickness, and patient satisfaction.Materials and methodsThis retrospective study included 327 patients who underwent hysteroscopy for AUB between January 2021 and January 2024 at a tertiary care center. Patients with incomplete records, inadequate follow-up, technically unsuccessful procedures, concurrent major surgeries, or endometrial cancer were excluded. Postoperative menstrual bleeding was assessed using the Pictorial Blood Loss Assessment Chart (PBAC). Data were analyzed using SPSS version 26, and p < 0.05 was considered statistically significant.ResultsOf the 327 patients included in the study, 91.1% had a baseline PBAC score ≥100, which significantly decreased following hysteroscopy (mean reduction: 393 points; p < .001). Postoperative Hemoglobin (Hb) levels and Endometrial Thickness (ET) also improved significantly in patients with high initial bleeding scores. Overall complication rate was low (6.4%), and 87% of patients reported satisfaction and willingness to recommend the procedure. McNemar analysis confirmed a significant shift from high to low bleeding severity postoperatively (p < .001).ConclusionsHysteroscopy demonstrated clinical efficacy in the management of abnormal uterine bleeding. Assessment using the PBAC score provided a feasible and informative method for quantifying treatment response, supporting its role as a valuable tool in the objective evaluation of bleeding outcomes.